KARAKTERISASI PENINGKATAN KEMAHIRAN BAHASA INGGRIS MELALUI REKONTRUKSI TERJEMAHAN TEKS TANTRI KANDAKA - IDA AYU MARTINI, I KETUT WARDANA, (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
This study aimed to strengthen positive learning character, to improve comprehensionin sentence construction and to develop their writing skill. The study made use an actionresearch design with descriptive analysis. The instruments used in the study were in the formsof test items, observation sheet and questioner. The application of the learning model wasconducted in two cycles each of which consisted two sessions. The scopes of the measurementwere focused on affective domain, cognitive domain and psyhomotoric domain. Theeffectiveness of the study could be seen from the increasing main score in every post testtowards the result of pretest and changing learning attitude. The success indicator of the studywas stated that 80% of the students could achieve the minimum passing grade; 75. Based onthe data analysis, 21 students achieved high competency and 17 students got average level.From the character side view, it was observed that 30 students (86%) were active, 33 students(87%) was cooperative and 36 students (94%) had great responsibility. From the finding, itcan be concluded that the ability of students under study in writing English was categorizedhigh and the positive character was more than 50 % culturalizedKey Words: recontruction, translation, character, Tantri Kandaka